Crystal structure of bis(N,N,N-triethylammonium) bis(tetraselenido-κ2Se1,Se4)palladate(II), C12H32N2PdSe8 - Kim Kang-Woo; Kim Jinhee (Zeitschrift für Kristallographie - New Crystal Structures, 2015)
C12H32N2PdSe8, orthorhombic, Pca21 (no. 29), a = 17.493(3) Å, b = 8.109(1) Å, c = 17.326(2) Å, V = 2457.6 Å3, Z = 4, Rgt(F) = 0.0270, wRref(F2) = 0.0565, T = 173 K.